DETERMINAN PERILAKU KONSUMTIF PADA SISWA JURUSAN IPS KABUPATEN TEGAL - M Fathur Rahman (Equilibria Pendidikan : Jurnal Ilmiah Pendidikan Ekonomi, 2023)
Consumptive behavior is an act of buying goods or services in excess without rationality, prioritizing wants over needs. Consumptive behavior caused by changes in individual lifestyles and encouragement from the environment. The purpose of this study focused on analyzing the effect of lifestyle, economic literacy on consumptive behavior with peer conformity as a moderating variable in social studies students at SMA N 2 Slawi. This study is quantitative approach with the research design causality. The method used is the survey method. The population is the students of class X and XI of Social Sciences Department of SMA N 2 Slawi, totaling 288 students and the sample used in this research is 168 students using the inverse square root method. The sampling technique was proportionate random sampling. Data collection techniques using questionnaires and data analysis techniques using descriptive analysis and SEM-PLS. The results are (1) lifestyle had a positive and significant effect with coefficient 0.380, (2) literacy economic had negative and significant with coefficient -0.131 (3) peer conformity moderated lifestyle on consumptive behavior with a coefficient 0.149 and (4) conformity peers can’t moderate the effect of economic literacy on consumptive behavior with coefficient 0.07 and  significance 0.194.